Processed by‐products from soy beverage (Okara) as sustainable ingredients for nile tilapia (o. niloticus) juveniles: effects on nutrient utilization and muscle quality - Voss, Glenise B. (2021)
The apparent digestibility coefficients (ADCs) of differently processed okara meals were assessed in Nile tilapia diets: dried okara not autoclaved (FOK), dried okara autoclaved (AOK), okara hydrolyzed with Alcalase (ALOK) or Cynara cardunculus proteases (CYOK), and hydrolyzed okara fermented with lactic bacteria: Lactobacillus rhamnosus R11 (CYR11OK) or Bifidobacterium animalis ssp. lactis Bb12 (CYB12OK). Okara processing significantly affected nutrient digestibility: dry matter ADC was highest in CYR11OK (80%) and lowest in FOK (40%). The lowest protein digestibility was observed in CYR11OK (72%), and the highest in AOK (97%) and CYOK (91%), evidencing the effectiveness of the autoclave and the use of C. Cardunculus proteases to increase okara protein bioavailability. The inclusion of up to 20% of AOK or CYOK did not affect fish growth, nutrient utilization, or whole body composition of Nile tilapia. The flesh quality (color, pH, water activity, cohesiveness, elasticity and resilience) was not affected by the dietary incorporation of AOK or CYOK. Fish fed with AOK diets stand out for their high density of muscle fibers, particularly in AOK20, which can explain their high muscle firmness and may result in further hypertrophic growth. Altogether, results suggest that hydrolyzed or autoclaved okara are valuable ingredients for Nile tilapia diets.